Aspirin therapy is associated with less compact fibrin networks and enhanced fibrinolysis in patients with abdominal aortic aneurysm. (12th March 2015) - Bailey, M. A.; Aggarwal, R.; Bridge, K. I.; Griffin, K. J.; Iqbal, F.; Phoenix, F.; Purdell‐Lewis, J.; Thomas, T.; Johnson, A. B.; Ariëns, R. A. S.; Scott, D. J. A.; Ajjan, R. A.
Summary Objective Thrombotic changes in fibrin networks contribute to increased cardiovascular risk in patients with abdominal aortic aneurysm (AAA). Given that aspirin modulates the fibrin network, we aimed to determine if aspirin therapy is associated with changes in ex‐vivo fibrin clot characteristics in AAA patients and also conducted an exploratory analysis of 5‐year mortality in these individuals. Methods We recruited 145 male patients, divided into controls (aortic diameter < 3 cm, n = 49), AAA not taking aspirin (AAA−Asp, n = 50) and AAA on 75 mg day−1 aspirin (AAA+Asp, n = 46), matched for aneurysm size. Characteristics of clots made from plasma and plasma‐purified fibrinogen were investigated using turbidimetric analysis, permeation studies, and confocal and electron microscopy. Plasma fibrinogen, D‐dimer and inflammatory marker levels were also measured. Results Maximum absorbance (MA) of plasma clots from controls was lower than that of AAA patients not on aspirin (AAA−Asp) at 0.30 ± 0.01 and 0.38 ± 0.02 au, respectively (P = 0.002), whereas aspirin‐treated subjects had MA similar to controls (0.31 ± 0.02 P = 0.9). Plasma clot lysis time displayed an identical pattern at 482 ± 15, 597 ± 24 and 517 ± 27 s for control, AAA−Asp and AAA+Asp (P = 0.001 and P = 0.8). The lysis time of clots made from purified fibrinogen of AAA−Asp was longer than that of AAA+Asp patients (756 ± 47 and 592 ± 52 s, respectively; P = 0.041). Permeation studies and confocal and electron microscopy showed increased clot density in AAA−Asp compared with the AAA+Asp group. Mortality in AAA−Asp and AAA+Asp was similar, despite increased cardiovascular risk in the latter group, and both exhibited higher mortality than controls. Conclusion Aspirin improves fibrin clot characteristics in patients with AAA, which may have important clinical implications.